KEKERASAN SEKSUAL SEBAGAI JARIMAH: STUDI KOMPARATIF ANTARA HUKUM JINAYAT DAN HUKUM POSITIF INDONESIA - Habibi Nasution, Syahnan; Fahri Rangkuti, Ryan; Hidayat Batubara, Taufik; Azhad Azizan S. Meliala, Azri; Hakim, Ikhwan (Pengelola Jurnal Politeknik Negeri Ketapang, 2025)
Sexual violence is a form of crime that destroys human dignity and human rights, and has widespread social and psychological impacts. In Islamic law, sexual violence is categorised as a crime with strict penalties, depending on the form and severity. On the other hand, Indonesian positive law has also given serious attention through the enactment of Law No. 12 of 2022 on Sexual Violence Crimes (UU TPKS). This article aims to compare the approaches of Islamic criminal law and Indonesian positive law in addressing sexual violence, both from a conceptual perspective, criminal elements, the process of proof, and the form of penalties